Dislodgement Forces and Cost Effectiveness of Dressings and Securement for Peripheral Intravenous Catheters: A Randomized Controlled Trial - Axel Schmutz (Journal of Clinical Medicine, 2020)
Objectives: Peripheral intravenous catheters (PIVC) are the most frequently used invasive devices in medicine. PIVC failure before treatment completion is a significant concern and occurs in 33–69% of patients. Partial dislodgement and accidental removal are some of the reasons for PIVC failure. The most effective dressing and securement method for preventing accidental removal remains unclear. It was the aim of this study to compare the force required to dislodge a PIVC with four commonly used dressing and securement methods. Additionally, costs were calculated. Methods: Truncated 18-gauge i.v. cannulas were attached onto the forearm of 209 volunteers using four different dressings and securements (sterile absorbent wound dressing covered by two different types of elastic polyester fleece, bordered and non-bordered polyurethane). The force during continuously stronger pulling until dislodgement was recorded. Results: The highest resistance against dislodgement forces could be observed with a sterile absorbent wound dressing covered by two incised elastic polyester fleece dressings. Commercially-manufactured bordered and non-bordered polyurethan film dressings were 20% to 75% more expensive than sterile absorbent wound dressings covered by elastic polyester fleece dressing. Conclusions: Elastic polyester fleece secured a PIVC against accidental removal by external force best, compared to commercially-manufactured bordered and non-bordered polyurethane film dressing.